Assessment of Arthroscopic Anterior cruciate ligament Reconstruction in Basrah - Ahmed Hazim Al Aoodh; Ahmed Ibrahim Habib Alobaidi; Nabeel Yousif Abdullah; Midhat M Mahdi (Basrah Journal of Surgery, 2024)
Background: Anterior cruciate ligament (ACL) injuries are common, particularly among young, active individuals, and are associated with significant morbidity. Arthroscopic ACL reconstruction has become the gold standard for restoring knee stability and function, yet the optimal candidate and timing for surgery remain subjects of ongoing research. Patients and Methods: This descriptive follow-up study, conducted at Basra Teaching Hospital from October 2011 to January 2014, enrolled 35 male patients aged 18-65 years with confirmed ACL injuries. Participants underwent arthroscopic ACL reconstruction using hamstring and gracilis tendon grafts. Outcomes were assessed using the Tegner-Lysholm scoring system, focusing on knee function and stability, over one year post-surgery. Statistical analyses were performed using SPSS version 26, with significance set at p < 0.05. Results: The majority of participants (62.8%) were aged 21-30 years, with a mean age of 24.6 ± 2 years. Right knee injuries were more common (57.1%). Most injuries (82.8%) were sports-related, predominantly from contact sports (74.3%). Post-operatively, significant improvements were observed in knee stability tests: Lachman test positive rates dropped from 100% to 5.7%, Pivot Shift test rates from 71.4% to 5.7%, and Anterior Drawer test rates from 100% to 14.2% (p < 0.001). The Tegner-Lysholm scores showed substantial enhancement, with poor outcomes decreasing from 48.5% to 5.7% and excellent ratings increasing from 0% to 22.8% (p < 0.001). Professional athletes had better recovery outcomes (average score 91.7) compared to non-professionals (average score 79.9, p = 0.041). Complications were minimal, with infection and ACL failures each occurring in 5.7% of cases, and leg-foot paresthesia in 2.8%. Conclusion: Arthroscopic ACL reconstruction is effective in significantly improving knee function and stability among young, active males, particularly those engaged in professional sports. Early surgical intervention, coupled with tailored rehabilitation, is crucial in achieving optimal outcomes. These findings advocate for a proactive approach in managing ACL injuries